2022
DOI: 10.1136/bmjopen-2021-057957
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of community-acquired pneumonia among hospitalised children in Indonesia: a multicentre, prospective study

Abstract: ObjectiveTo identify aetiologies of childhood community-acquired pneumonia (CAP) based on a comprehensive diagnostic approach.Design‘Partnerships for Enhanced Engagement in Research-Pneumonia in Paediatrics (PEER-PePPeS)’ study was an observational prospective cohort study conducted from July 2017 to September 2019.SettingGovernment referral teaching hospitals and satellite sites in three cities in Indonesia: Semarang, Yogyakarta and Tangerang.ParticipantsHospitalised children aged 2–59 months who met the crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
1
11
0
1
Order By: Relevance
“…It causes significant morbidity and necessitates hospitalization in young children. 1 The infection occurs in all age groups, but most children are infected at or before 2 years of age. 2 Patients with HRSV bronchiolitis usually present with two to four days of upper respiratory tract symptoms such as fever, rhinorrhea, and congestion, followed by lower respiratory tract symptoms such as increasing cough, wheezing, and increased respiratory effort.…”
Section: Introductionmentioning
confidence: 99%
“…It causes significant morbidity and necessitates hospitalization in young children. 1 The infection occurs in all age groups, but most children are infected at or before 2 years of age. 2 Patients with HRSV bronchiolitis usually present with two to four days of upper respiratory tract symptoms such as fever, rhinorrhea, and congestion, followed by lower respiratory tract symptoms such as increasing cough, wheezing, and increased respiratory effort.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, a study in Indonesia found that Hib is one of the pathogens responsible for causing pneumonia that requires hospitalization among Indonesian children aged 2–59 months old. Hib conjugate vaccine programs have alleviated the global burden of Hib meningitis in children [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet discriminating bacterial and viral etiologies of pneumonia in children remains challenging ( 2 ). Despite evidence that appropriate antibiotics are lifesaving, in low-resource settings, rational selection of antibiotics for pneumonia is hampered by limited access to gold standard diagnostic tests, which are often costly and require specialized equipment and techniques ( 3 , 4 ). Consequently, healthcare providers, particularly those in low-income and middle-income countries (LMIC), likely overtreat non-bacterial pneumonia with antibiotics, which may accelerate development of antimicrobial resistance (AMR) ( 2 , 3 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Partnerships for Enhanced Engagement in Research-Pneumonia in Pediatrics (PEER-PePPeS) study was a multisite observational cohort study in Indonesia designed to identify etiologies of childhood CAP using comprehensive diagnostic methods ( 4 ). Causative bacterial, viral or mixed viral-bacterial pneumonia pathogens were determined using a previously published algorithm based on microbiological, molecular and serological testing as the gold standard ( 2 ).…”
Section: Introductionmentioning
confidence: 99%